Desain Software-Defined Networking (SDN) Berbasis Nano AI Untuk Skalabilitas Jaringan Cloud (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Rapid digital transformation demands flexible, automated, and scalable network solutions. Software-Defined Networking (SDN) serves as the foundation of modern networks, yet its management requires enhanced intelligence to support cloud service scalability. This article proposes an SDN design based on nano AI, which is a micro-artificial intelligence system for real-time automated network management. A Research and Development approach is utilized to develop the prototype and system model. Experimental results demonstrate a 43% increase in network management efficiency, a 27% reduction in latency, and a significant improvement in cloud system scalability.